In vivo effect of some fungicides on the development of Pyricularia grisea and Helminthosporium oryzae - Douira, A.; Mouria, A.; Ouazzani Touhami, A.; Serghat, S. (Phytopathologia Mediterranea, 2002)
The effect of various fungicide treatments of seeds and leaves of rice on the development of the pathogenic fungi Pyricularia grisea and Helminthosporium oryzae was studied. When applied to seeds, tricyclazole, mancozeb and the carboxin+thiram combination were the only fungicides that reduced all the symptoms induced by both pathogens without damaging the development of young plants. Tricyclazole and the tricyclazole+mancozeb protected rice plants against P. grisea and H. oryzae respectively throughout the vegetative phase. To ensure protection during the entire vegetative phase, pyrazophos should be applied every two weeks while the carboxin+thiram combination, thiabendazole and mancozeb should be applied every week.